Alkaloids as Photosensitisers for the Inactivation of Bacteria - Sònia López-Molina; Cristina Galiana-Roselló; Carolina Galiana; Ariadna Gil-Martínez; Stephane Bandeira; Jorge González-García (MDPI AG, 2021)
Antimicrobial photodynamic therapy has emerged as a powerful approach to tackle microbial infections. Photodynamic therapy utilises a photosensitiser, light, and oxygen to generate singlet oxygen and/or reactive oxygen species in an irradiated tissue spot, which subsequently react with nearby biomolecules and destroy the cellular environment. Due to the possibility to irradiate in a very precise location, it can be used to eradicate bacteria, fungus, and parasites upon light activation of the photosensitiser. In this regard, natural products are low-cost molecules capable of being obtained in large quantities, and some of them can be used as photosensitisers. Alkaloids are the largest family among natural products and include molecules with a basic nature and aromatic rings. For this study, we collected the naturally occurring alkaloids used to treat microorganism infections using a photodynamic inactivation approach. We gathered their main photophysical properties (excitation/emission wavelengths, quantum yields, and oxygen quantum yield) which characterise the ability to efficiently photosensitise. In addition, we described the antibacterial activity of alkaloids upon irradiation and the mechanisms involved in the microorganism killing. This review will serve as a reference source to obtain the main information on alkaloids used in antimicrobial photodynamic therapy.